Comparative Bioavailability Study of Two Cefixime Formulations Administered Orally in Healthy Male Volunteers - Zakeri-Milani, Parvin; Valizadeh, Hadi; Islambulchilar, Ziba (Arzneimittelforschung, 2008)
The bioavailability of a new Cefixime ((6R,7R)-7-[(Z)-2-(2-amino-4-thiazolyl)-2-(carboxymethoxyimino) acetamido]-8-oxo-3-vinyl-5-thia-l-azabicyclo-[4,2,0]-oct-2-ene-2-carboxylic acid, CAS 79350-37-1) tablet preparation (Loprax®) was compared with that of a reference preparation of the drug in 24 healthy male volunteers. The trial was designed as an open, randomized, single-blind, two-sequence, two-period crossover study. Under fasting conditions, each subject received a single oral dose of 400 mg Cefixime tablet as a test or reference formulation on 2 treatment days. The treatment periods were separated by a one-week washout period. The plasma concentrations of the drug were analyzed by a rapid and sensitive HPLC method with UV detection. The pharmacokinetic parameters included AUC0–24h, AUC0–infinity, Cmax, t1/2, and Ke. The mean AUC0-infinity of Cefixime was 45008.7 ± 10989.9 and 45221.3 ± 2155.7 n · h/ml for the test and reference formulation, respectively. The maximum plasma concentration (Cmax) of Cefixime was on average 4746.9 ± 1284 ng/ml for the test and 4726.3 ± 1206.9 ng/ml for the reference product. No statistical differences were observed for Cmax and the area under the plasma concentration-time curve for test and reference tablets. The calculated 90% confidence intervals based on the ANOVA analysis for the mean test/reference ratios of Cmax, AUC0.intlnlty and AUC0–24h of Cefixime were in the bioequivalence range (94%–l 12%). Therefore, the two formulations were considered to be bioequivalent.
Keywords: Antibiotics, cephalosporin; CAS 79350-37-1; Cefixime, bioavailability, bioequivalence; Loprax®